Total Bioavailable Organic Selenium in Fishmeal-Based Diet Influences Growth and Physiology of Juvenile Cobia Rachycentron canadum (Linnaeus, 1766) - Pham, Hung Duc; Siddik, Muhammad; Fotedar, Ravi; Nguyen, C.; Nahar, A.; Gupta, Sanjay (Humana Press, Inc., 2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. The study examined the effects of supplemental organic selenium (Se) extracted from selenoyeast on the growth performance, glutathione peroxidase (GPx) activity, biochemical status and liver histochemistry of juvenile cobia Rachycentron canadum. Six experimental diets were prepared supplemented with Se with total concentration of 1.52 (Se-1.52), 1.93 (Se-1.93), 2.29 (Se-2.29), 2.71 (Se-2.71) and 3.14 (Se-3.14) mg/kg of total Se in the diets and a fishmeal-based control diet without Se supplementation containing 1.15 (Se-1.15) mg/kg of Se was used as control. Experimental diets were fed to the fish of six treatment groups in triplicate twice daily for 8 weeks. Juvenile cobia fed dietary Se of 1.93, 2.29 and 2.71 mg/kg showed increased final body weight (FBW), specific growth rate (SGR) and feed intake (FI) than the fish fed the control diet. Se accumulations in the muscle and liver tissue displayed a positive linear relationship with dietary Se levels. Se deficiency was apparent in fish fed the control diet and displayed reduced growth and feed efficiency. Red blood cell (RBC) counts were significantly (P < 0.05) higher in cobia fed dietary Se between 1.52 to 2.71 mg/kg than the fish fed 3.14-mg/kg Se diet. Glutathione peroxidase activity significantly (P < 0.05) declined in the group fed with control diet compared to fish fed Se-supplemental diet. Juvenile cobia fed the highest Se level (Se-3.14 mg/kg) showed toxic effects in the liver, including histopathological lesions in the liver. Based on the results obtained for FBW, SGR, tissue Se retention and haematological parameters, we conclude that optimal dietary Se requirement for juvenile cobia fed commercial diets is 2.32 mg/kg.